(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon our most honorable Prophet Muhammad Al-Mustafa Al-Amin, his good and pure family, and his chosen companions. To proceed: